Interest in Professional Transfer as a Youtuber in Ponorogo Regency - Anggoro, Ayub Dwi; Susanto, Happy; Arifin, Rizal; Nugroho, Oki Cahyo; Purwati, Eli; Ridho, Irvan Nur (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Technological changes that are increasingly developing cause different services and facilities in the field of information and communication technology. Youtuber is part of the content creator as a profession that requires creativity with several skills. Another definition refers to the content of content creators who call themselves YouTubers, this happens because the label has a meaning that is considered a profession. This is one of the global professions of creative workers, who can produce monetized content as a form of income earned through the creativity of content creators. This is what most of the general public, especially millennials, interpret about the YouTuber profession. This study uses library research, where researchers use library research methods. The main differences between library research and field research lie in the purpose, function and/or location of library research in each of these studies. In library research, library research is more than just a service function such as: As a first step in preparing a research framework and/or proposal to obtain similar research information. This study aims to determine the change of profession as a YouTuber in the existing community. Thus, based on the results of the discussion, it is found that youtubers as content creators are influenced by many factors, namely ideas, the accuracy of the selection of shooting equipment, and the ability to master the material.